解方程2x^5-x^4-15x^3+9x^2+16x+4
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 23:21:16
解方程2x^5-x^4-15x^3+9x^2+16x+4解方程2x^5-x^4-15x^3+9x^2+16x+4解方程2x^5-x^4-15x^3+9x^2+16x+42x^5-x^4-15x^3+9
解方程2x^5-x^4-15x^3+9x^2+16x+4
解方程2x^5-x^4-15x^3+9x^2+16x+4
解方程2x^5-x^4-15x^3+9x^2+16x+4
2x^5-x^4-15x^3+9x^2+16x+4
=(x²+3x+1)(x-2)²(2x+1)
{-1/2,2,(-3 - Sqrt[5])/2,(-3 + Sqrt[5])/2}
1x+2x+3x+4x+5x+6x+7x+8x+9x+10x+11x+12x+13x+14x+15x=550必须用解方程
解方程2x^5-x^4-15x^3+9x^2+16x+4
解方程2x^5-x^4-15x^3+9x^2+16x+4
解方程2/(x+8)+5/(x+9)=3/(x+15)+4/(x+6)
解方程(x-3/x)-(3-x/x+1)=5x-15/2x+2
解方程:(x-2)(x^2-6x-9)=x(x-5)(x-3)
解方程 x(2x-4)+3x(x-1)=5x(x-3)+8
解方程:x(3x-4)+2x(x+7)=5x(x-7)+90
解分式方程 x-7/x-9+x-3/x-5=x-4/x-6+x-6/x-8
解方程 x-7/x-9+x-3/x-5=x-4/x-6+x-6/x-8
解方程:(x+3)/(x+2)-(x+4)/(x+3)=(x+5)/(x+4)-(x+2)/(x+1)
解方程:(x-8)/(x-3)-(x-9)/(x-4)=(x+7)/(x+8)-(x+2)/(x+3)
解方程(x-2)X(x的平方-6x-9)=x(x-5)X(x-3)
解方程(x-2)/(x-3)-(x-3)/(x-4)=(x-5)/(x-6)-(x-6)/(x-7)
解方程 x+2/x+1+x+8/x+7=x+6/x+5+x+4/x+3
解方程:2x+4x+6x...+100x=1-(x+3x+5x+...+99x)
解方程 (x+2)/(x+1) - (x+4)/(x+3)=(x+6)/(x+5)-(x+8)/(x+7)
1+x+x^2+x^3+x^4+x^5+x^6+x^7+x^8+x^9+x^10+x^11=17.7这个方程怎么样求解?